BIOM-40. TARGETED GENE EXPRESSION PROFILING PREDICTS MENINGIOMA OUTCOMES AND RADIOTHERAPY RESPONSES. (12th November 2021) - Chen, William; Choudhury, Abrar; Vasudevan, Harish; Lucas, Calixto; Nguyen, Minh; Young, Jacob; Yu, Theresa; Lam, Tai-Chung; Pu, Jenny; Li, Lai-Fung; Leung, Gilberto; Chan, Jason; et al.
Abstract: BACKGROUND: Surgery is the mainstay of meningioma treatment, but improvements in meningioma risk stratification are needed and indications for postoperative radiotherapy are controversial. DNA methylation profiling, copy number variants (CNVs), exome sequencing, and RNA sequencing have improved understanding of meningioma biology, but have not superseded histologic grading, or revealed biomarkers for radiotherapy responses. To address these unmet needs, we optimized and validated a targeted gene expression biomarker predicting meningioma outcomes and responses to radiotherapy. METHODS: Targeted gene expression profiling was performed on a discovery cohort of 173 meningiomas (median follow-up 8.1 years) and a validation cohort of 331 meningiomas (median follow-up 6.1 years) treated with surgery (n=504) and postoperative radiotherapy (n=73) at independent, international institutions (70% WHO grade 1, 24% WHO grade 2, 6% WHO grade 3). Optimized targeted gene expression models predicting clinical outcomes (34 genes) or radiotherapy responses (12 genes) were developed from the discovery cohort, and compared to histologic and molecular classification systems by performing DNA methylation profiling, CNV analysis, exome sequencing, and RNA sequencing on the same meningiomas. RESULTS: Targeted gene expression profiling achieved a concordance-index of 0.75 ± 0.03 (SEM) for local freedom from recurrence (LFFR) and 0.72 ± 0.03 for overall survival (OS) in the validation cohort, outperforming WHO grade (5-year LFFR delta-AUC 0.15, 95% CI 0.076-0.229, p=0.001) and DNA methylation grouping (delta-AUC 0.075, 95% CI 0.006-0.130, p=0.01) for LFFR, disease-specific survival, and OS. The biomarker was independently prognostic after accounting for WHO grade, extent of resection, primary versus recurrent presentation, CNV status, DNA methylation group, and Ki67 labeling index, and identified meningiomas benefiting from radiotherapy (interaction p-value=0.0008), suggesting postoperative radiotherapy could be refined in 30.2% of cases. CONCLUSIONS: Targeted gene expression profiling of 504 meningiomas improves discrimination of meningioma local recurrence, disease-specific survival, and overall survival, and predicts radiotherapy responses.